Lifestyle Entrepreneurship in Tourism Innovations, Sustainability, and Marketing Practices - Dias, Á. (2025)
This book delves into the emerging field of tourism lifestyle entrepreneurship exploring its unique characteristics, challenges, and contributions to the tourism industry and broader economy. Designed for both academic researchers and aspiring entrepreneurs, this book provides a nuanced understanding of the motivations, innovations, and sustainability practices that define this sector. It examines the distinct qualities that set lifestyle entrepreneurs apart from traditional business owners, highlighting their pursuit of personal fulfilment and work-life balance alongside financial success.